Time and productivity loss associated with immunotherapy infusions for the treatment of melanoma in the United States: a survey of health care professionals and patients - Raquel Aguiar-Ibáñez; Emilie Scherrer; Dmitri Grebennik; John Cook; Shalini Bagga; Baanie Sawhney; Anvi Khandelwal; Scott A. Soefje (BMC, 2023)
Abstract Introduction A new dosing schedule for the oncology immunotherapy pembrolizumab, every 6 weeks (Q6W), has been approved by the U.S. FDA, reducing the frequency of visits to infusion centers. We quantified the time spent by oncologists, nurses, patients, and caregivers per melanoma-related immunotherapy infusion visit to evaluate its potential impact. Methods Surveys were self-completed by 100 oncologists, 101 oncology nurses, and 100 patients with melanoma across the U.S. to quantify the time spent per infusion visit with pembrolizumab (Q3W or Q6W), nivolumab (Q2W or Q4W), or nivolumab+ipilimumab (nivolumab in combination: Q3W; nivolumab maintenance: Q2W or Q4W). Time measures included traveling, waiting, consultation, infusion, post-treatment observation, and caregiving. Respondents were also surveyed regarding the impact of the COVID-19 pandemic on infusion treatments. Results Responses deemed valid were provided by 89 oncologists, 93 nurses, and 100 patients. For each new [returning] patient treated with pembrolizumab, nivolumab or nivolumab+ipilimumab, oncologists reported to spend an average of 90 [64], 87 [60] and 101 [69] minutes per infusion visit (p-value for between-group difference = 0.300 [0.627]). For first [subsequent] treatment cycles, nurses reported spending 160 [145] average minutes per visit for nivolumab+ipilimumab, versus roughly 120 [110] for the single agents (p-value for between-group difference = 0.018 [0.022]). Patients reported to spend an average of 263, 382, and 224 minutes per visit at the center for pembrolizumab (N = 47), nivolumab (n = 34), and nivolumab+ipilimumab (n = 15) respectively (p-value for between-group difference = 0.0002). Patients also reported that their unpaid (N = 20) and paid caregivers (N = 41) spent with them an average of 966 and 333 minutes, respectively, from the day before to the day after the infusion visit. Conclusion Less frequent immunotherapy infusion visits may result in substantial time savings for oncologists, nurses, patients, and caregivers.